Can Tocqueville karaoke? - Clark, Terry Nichols, 1940- (Research in urban policy ;, 2014)
This volume questions the importance of arts and culture and their possible impact on politics and the economy. Chapters outline a new framework for analysis of democratic participation and economic growth and explore how these new patterns work around the world. The ideas of Alexis de Tocqueville and Joseph Schumpeter and Jane Jacobs are analysed.